Linguistics : a complete introduction - Hornsby, David, 1963- (London: Hodder & Stoughton, 2014)
A comprehensive yet easy-to-use introduction to understanding linguistics. Hornsby explains linguistic thought, syntax, sound systems, language acquisition, and much more. This book will be helpful whether you are studying for an exam or essay, or you simply want to improve your knowledge.
Thinking like a linguist -- A brief history of linguistic thought -- Structural linguistics -- The building blocks of language: describing speech sounds -- Laying the foundations: sound systems in language -- Building words: morphology -- A grammar of sentences: syntax -- The Chomskyan revolution: generative grammar -- Semantics: the meaning of "meaning" -- Pragmatics: saying what you mean -- Exploring variation in language -- Choosing your language: multilingualism and language planning -- Mechanisms of language change.
Includes index.
At the head of the title: Teach yourself.
Includes bibliographical references (pages 295-303) and index.
Keywords: Linguistics; Linguistique; linguistics; Linguistics